2023
DOI: 10.1007/s00432-023-05031-3
|View full text |Cite
|
Sign up to set email alerts
|

CSPG4 as a target for the specific killing of triple-negative breast cancer cells by a recombinant SNAP-tag-based antibody-auristatin F drug conjugate

Abstract: Purpose Triple-negative breast cancer (TNBC) is phenotypic of breast tumors lacking expression of the estrogen receptor (ER), the progesterone receptor (PgR), and the human epidermal growth factor receptor 2 (HER2). The paucity of well-defined molecular targets in TNBC, coupled with the increasing burden of breast cancer-related mortality, emphasizes the need to develop targeted diagnostics and therapeutics. While antibody–drug conjugates (ADCs) have emerged as revolutionary tools in the selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(33 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Thereafter, the recombinant fusion protein was either conjugated with the highly potent BG-IR700 or BG-modified AURIF, synthesized using a novel click chemistry coupling strategy, whereby an AURIF−linker−BG payload was created to autocatalytically react with the respective SNAP-tag fusion proteins. 7,40 Finally, our results validate the binding selectivity of the fusion protein (on African descendent-derived tumor biopsies and TNBC cells) and the selective phototoxic and antimitotic activity of the conjugates on several CD44expressing TNBC cells.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thereafter, the recombinant fusion protein was either conjugated with the highly potent BG-IR700 or BG-modified AURIF, synthesized using a novel click chemistry coupling strategy, whereby an AURIF−linker−BG payload was created to autocatalytically react with the respective SNAP-tag fusion proteins. 7,40 Finally, our results validate the binding selectivity of the fusion protein (on African descendent-derived tumor biopsies and TNBC cells) and the selective phototoxic and antimitotic activity of the conjugates on several CD44expressing TNBC cells.…”
Section: Introductionsupporting
confidence: 72%
“…Finally, the αCD44(scFv)-SNAPf recombinant fusion protein was purified out of the transfected cells free supernatants via the C-terminal 6xHis-tag (immobilized Metal Affinity Chromatography: IMAC), using a Ni 2+ sepharose column on an A ̈KTA protein purification system (GE Healthcare Europe GmbH, Freiburg, Germany) as described elsewhere. 7,40 2.3. SDS-PAGE and Western Blotting.…”
Section: Cell Culturementioning
confidence: 99%
“…Among the proteoglycans, NG2 is a large cell-surface antigen and an unusual cell membrane integral glycoprotein which was reported to play an important role in tumor cell growth, metastasis and survival as a high-affinity receptor for extracellular proteins, growth factors and integrins [ 14 ]. Although the biological significance underlying NG2 proteoglycan involvement in cancer progression needs to be better defined, the expression of NG2 is closely associated with the poor prognoses in hepatocellular carcinoma, pancreatic malignancy and anaplastic thyroid cancer [ 27 – 29 ]. Importantly, NG2-specific monoclonal antibodies (mAbs) have been evidenced to inhibit tumor cell growth and metastasis [ 30 ], but have not been approved by the FDA yet.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, NG2-specific monoclonal antibodies (mAbs) have been evidenced to inhibit tumor cell growth and metastasis [ 30 ], but have not been approved by the FDA yet. Besides, the latest studies have shown intense preclinical activity of NG2-targeting technology in both melanoma and breast cancer, further supporting NG2 as a valuable target in cancer therapy [ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, our previous study ( 14 ) revealed that expression of CSPG4P12 was decreased in NSCLC tissues compared to normal lung tissues, and overexpressed CSPG4P12 significantly inhibited lung cancer cell proliferation, migration, invasion, and adhesion. CSPG targeting antibody-drug conjugate showed a strong toxic effect on cancer cells in a concentration-dependent manner ( 21 ). Furthermore, CSPG4 -specific mAb has been shown to inhibit growth, adhesion, and migration of cancer cells in vitro , and significantly reduces the tumorigenic power of cancer cells and mitigates metastases and recurrence in vivo ( 22 ).…”
Section: Discussionmentioning
confidence: 99%